الحماية الجزائية لحياء و عرض الطفل – دراسة مقارنة – في الفقه الإسلامي و القانون الجنائي الجزائري - موساوي, فايزية (University of Eloued جامعة الوادي, 2017)
اعز ما نملك في الحياة أطفالنا ,نسعى إلى إسعادهم وحمايتهم من كل ما يدنس حياتهم , لذلك أحاطتهم أحكام الشريعة بالرعاية والعناية وعمل المجتمع الدولي, والتشريع الداخلي على توفير الحماية لهم. تتضمن الدراسة تحليل دور التشريع الجنائي الجزائري في توفير الحماية الجزائية لحياء وعرض الطفل, من الاعتداءات الجنسية التي يكون ضحيتها, من يوم ولادته إلي حين بلوغه 18سنة كاملة. ومدى تبنيه لسياسة جنائية هادفة, مقارنة بما قدمته الشريعة الإسلامية من أحكام لحماية و صيانة الأخلاق والأعراض في مجال التجريم و العقاب , وفي مراحل الدعوى, ومن جهة أخري في مجال اتخاذ التدابير اللازمة لحمايته Dearest what we have in our life is our children .We work hard to protect them and make them happy against every things desecrates their life. The provisions of the law give them the care, and interest ;in other word the International Internal Gislation worked on to protection for this fragile weak group. This analytical studying include the role of Algerian Criminal Gislation to provide pently protection to child life and symptom from sexual violence who is victim by its from birth to puberty 18 years .to what extant chaff to purpose penatly politices;comparison between what the Provisions of Islamic Jurispundence provided the provision ;and maintenance of ethics ;and sympotoms in the field of crime; and punishment in the stages of the proceeding in other way in the failed of necessary measures taken.
مذكرةماستر تخصص شريعة وقانون
Keywords: حياء –عرض – الطفل -الحماية الجزائية - الإجراءات; shyness - width - child - criminal protection - procedures